Avaliação da resistência flexural de resinas acrílicas termoativadas: influência do tempo de prensagem e armazenagem pós-polimerização - Bergamini, Larissa Ferreira da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The rehabilitation of edentulous patients by partial or complete or partial devices made of acrylic resin has been a successful option in dentistry. Is attributed to the success of the manufacture of acrylic resin base dentures to three factors: its excellent appearance, processing simple and easy to repair. As a disadvantage, devices made of acrylic resin can fracture in during chewing or even during hygiene procedures (these frequently) as a result of fatigue or low resistance of the material, highly influenced by pre-and post-polymerization: time pressing, temperature control, and storage polymerization cycle. The purpose of this study was to assess the importance of pressing time and storage of post-curing on the flexural strength of acrylic resins ® and Classic ® Plus Vipi Cril. 60 bodies were made-of-proof standard for each acrylic resin studied as Specification No. 12 of the American Dental Association (65 x 10 x 2.5 mm). The finish was done in lathe and polished with sandpaper following the sequence: 200, 500, 600, 800 and 1200. The body-of-evidence were divided into 12 groups (n = 10) distinguished: Group I - Vipi Cril Plus ® - Pressing conventional / Group II - Vipi Cril Plus ® - Pressing conventional storage + distilled water 24 hours / Group III - Vipi Cril Plus ® - Pressing conventional storage distilled water + 30 days / Group IV - Vipi Cril Plus ® - Pressing 24 / Vipi Cril Group V-Plus ® - Pressing 24 hours + 24 hours storage distilled / Group VI - Vipi Cril Plus ® - Pressing 24 hours + distilled water 30 days storage / Group VII - Classic ® - Pressing conventional / Group VIII - Classic - Pressing conventional storage + distilled water 24 hours / Group IX - Classic ® - Pressing conventional storage distilled water + 30 days / Group X - Classic ® - Pressing 24 / XI Group - Classic ® - Pressing 24 hours + 24 hours storage distilled...

A reabilitação de pacientes desdentados totais ou parciais por meio de dispositivos totais ou parciais confeccionados com resina acrílica tem representado uma opção bem sucedida na Odontologia. Atribui-se o sucesso da resina acrílica na confecção de base de próteses removíveis a três fatores: sua excelente aparência, o processamento simples e a reparação fácil. Como desvantagem, aparelhos confeccionados com resina acrílica podem se fraturar em durante a mastigação ou mesmo durante os procedimentos de higienização (estes mais freqüentes), como resultado de fadiga ou baixa resistência do material, altamente influenciada por fatores pré e pós-polimerização: tempo de prensagem, controle de temperatura, ciclo de polimerização e armazenagem. O propósito deste estudo foi verificar a importância do tempo de prensagem e da armazenagem pós-polimerização sobre a resistência flexural das resinas acrílicas Clássico® e Vipi Cril Plus®. Foram confeccionados 60 corpos-de-prova padronizados para cada resina acrílica estudada conforme a Especificação nº 12 da American Dental Association (65 x 10 x 2,5 mm). O acabamento foi feito em torno mecânico e o polimento com lixas seguindo a seqüência: 200, 500, 600, 800 e 1200. Os corpos-de-prova foram divididos em 12 grupos (n=10) distintos: Grupo I - Vipi Cril Plus® - Prensagem convencional/ Grupo II - Vipi Cril Plus® - Prensagem convencional + armazenagem 24 horas água destilada/ Grupo III - Vipi Cril Plus® - Prensagem convencional + armazenagem água destilada 30 dias/ Grupo IV - Vipi Cril Plus® - Prensagem 24 horas/ Grupo V- Vipi Cril Plus® - Prensagem 24 horas + armazenagem 24 horas água destilada/ Grupo VI - Vipi Cril Plus® - Prensagem 24 horas + armazenagem água destilada 30 dias/ Grupo VII - Clássico® - Prensagem convencional/ Grupo VIII...
Keywords: Prótese total; Polimetil metacrilato; Polimerização; Denture, Complete